2017
DOI: 10.1017/s1751731117000386
|View full text |Cite
|
Sign up to set email alerts
|

Age-related oxidative stress and antioxidant capacity in heat-stressed broilers

Abstract: We aimed to evaluate the effects of acute heat stress (HS) and age on the redox state in broilers aged 21 and 42 days. We evaluated the expression of genes related to antioxidant capacity, the production of hydrogen peroxide (H2O2), and the activity of antioxidant enzymes in the liver, as well as oxidative stress markers in the liver and plasma. The experiment had a completely randomized factorial design with two thermal environments (thermoneutral and HS, 38°C for 24 h) and two ages (21 and 42 days). Twenty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Compared to controls, heat-stressed TM chickens were previously reported to exhibit decreased catalase mRNA levels [13]. Moreover, broilers were found to exhibit higher levels of catalase activity during acute heat stress, but this antioxidant capacity decreased with age [51]. In female broilers, cardiac catalase activity was reduced after cold stimulation [52].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to controls, heat-stressed TM chickens were previously reported to exhibit decreased catalase mRNA levels [13]. Moreover, broilers were found to exhibit higher levels of catalase activity during acute heat stress, but this antioxidant capacity decreased with age [51]. In female broilers, cardiac catalase activity was reduced after cold stimulation [52].…”
Section: Discussionmentioning
confidence: 99%
“…For example, liver CAT activities were decreased under HS in bream [ 32 ]. Broilers with HS treatment also showed relative higher H 2 O 2 production compared with the regular ones [ 33 ]. In this study, we detected the activities of CAT, T-AOC, the content of H 2 O 2 and ·OH inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of four genetically distinct chicken lines with different feed efficiency showed that AHS (2 h) decreased FI in modern broilers (1995 random bred and modern random bred lines) but not in jungle fowl and Athens Canadian random bred chickens (Tabler et al, 2020). Several other studies have shown the negative impacts of HS on broiler chickens' performance (Del Vesco et al, 2017;Awad et al, 2020).…”
Section: Introductionmentioning
confidence: 89%